Para além do discurso oficial das políticas públicas: possibilidade de (re)pensar o paradigma de inclusão escolar para o educando com transtorno do espectro autista na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This paper aims to rethink the paradigm of inclusive education for learners with Autism Spectrum Disorder in Manaus beyond the official discourse of public policy. It is based on a qualitative study of bibliographical focusing on documentary analysis. The course of this research begins with historical background of special education in Brazil, according to the description of the etiology, conceptualization, behavioral characteristics and incidence of students with Autism Spectrum Disorder ( ASD ), in classes of regular schools in the city of Manaus, in the period from 2011 to 2013, and finally, it is the analysis of the National Policy on Special Education in the Perspective of Inclusive Education - PNEE-PEI/2008 and Policy of the city of Manaus watching your points and counterpoints with a view to inclusion the student with ASD. The analysis of the documents were made from the perspective of historical and dialectical materialism, whose documents reviewed include educational law, LDB No. 4.024/1961, Law No. 5.692/1971 and 9.394/1996 LDB paragraph, relating to special education, the Education Policy special - PNEE/1994 , which shows the integration process, the National Policy on special Education in the Perspective of inclusive Education - PNEE-PEI/2008, bringing the proposal of inclusive education, and statistical data referring to autistic students enrolled in regular teaching Manaus. The research result shows that advances in relation to special education happened gradually, changing the status of segregation of disabled people to the integration process and subsequently for inclusion. The new LDB 9.394/1996 devoted an entire chapter to special education, establishing guidelines and guiding services and resources in this type of education. The policy of the Ministry of Education Inclusion 2008 guarantees the right of everyone to education, access, permanence and continuity in regular education, the Educational Service Specialist - ESA, among other services. However, against the policy comes PNEE-PEI/2008 the city of Manaus, with the vision care clinic for people with Autistic Spectrum Disorder, considering them unable, without the possibility of development, with no prospect of inclusion and participation in the life social, seeing the pathology, the disease and not the potential of the autistic person, stigmatizing him on account of disability. Thus, it is expected that this work can contribute to reflections on the public policies implemented in the city of Manaus in care for people with Special Educational Needs - SEN, in particular to students with Autism Spectrum Disorder, seeing the development of their potential, their inclusion in the educational process and their full participation in social life.
Keywords: Políticas Públicas; Transtorno do Espectro Autista; Educação Especial; Educação Inclusiva; Inclusão Escolar; Public Policy; Autism Spectrum Disorder; Special Education; Inclusive Education; School Inclusion; CIÊNCIAS HUMANAS: EDUCAÇÃO